Totally drug‐resistant tuberculosis and adjunct therapies. (18th June 2014) - Parida, S. K.; Axelsson‐Robertson, R.; Rao, M. V.; Singh, N.; Master, I.; Lutckii, A.; Keshavjee, S.; Andersson, J.; Zumla, A.; Maeurer, M.
Abstract: The first cases of totally drug‐resistant (TDR) tuberculosis (TB) were reported in Italy 10 years ago; more recently, cases have also been reported in Iran, India and South Africa. Although there is no consensus on terminology, it is most commonly described as 'resistance to all first‐ and second‐line drugs used to treat TB'. Mycobacterium tuberculosis ( M.tb ) acquires drug resistance mutations in a sequential fashion under suboptimal drug pressure due to monotherapy, inadequate dosing, treatment interruptions and drug interactions. The treatment of TDR‐TB includes antibiotics with disputed or minimal effectiveness against M.tb, and the fatality rate is high. Comorbidities such as diabetes and infection with human immunodeficiency virus further impact on TB treatment options and survival rates. Several new drug candidates with novel modes of action are under late‐stage clinical evaluation (e.g. delamanid, bedaquiline, SQ109 and sutezolid). 'Repurposed' antibiotics have also recently been included in the treatment of extensively drug resistant TB. However, because of mutations in M.tb, drugs will not provide a cure for TB in the long term. Adjunct TB therapies, including therapeutic vaccines, vitamin supplementation and/or repurposing of drugs targeting biologically and clinically relevant molecular pathways, may achieve better clinical outcomes in combination with standard chemotherapy. Here, we review broader perspectives of drug resistance in TB and potential adjunct treatment options.